Mutational signatures reveal the dynamic interplay of risk factors and cellular processes during liver tumorigenesis - Eric Letouzé; Jayendra Shinde; Victor Renault; Gabrielle Couchy; Jean-Frédéric Blanc; Emmanuel Tubacher; Quentin Bayard; Delphine Bacq; Vincent Meyer; Jérémy Semhoun; Paulette Bioulac-Sage; Sophie Prévôt; et al. (Nature Communications, 2017)
Tumorigenesis is a complex process driven by numerous risk factors. Here, genomic analysis of liver cancer reveals the evolution of mutational signatures during tumor development, highlighting mutational and structural signatures linked to environmental exposures and endogenous cellular processes.